Optimization of asparaginase production from Zymomonas mobilis by continuous fermentation - Menegat, Francieli Bortoluzzi; Baldo, Cristiani; Celligoi, Maria Antonia Pedrine Colabone; Buzato, João Batista (Acta Scientiarum. Biological Sciences, 2016)
Asparaginase is an enzyme used in clinical treatments as a chemotherapeutic agent and in food technology to prevent acrylamide formation in fried and baked foods. Asparaginase is industrially produced by microorganisms, mainly gram-negative bacteria. Zymomonas mobilis is a Gram-negative bacterium that utilizes glucose, fructose and sucrose as carbon source and has been known for its efficiency in producing ethanol, sorbitol, levan, gluconic acid and has recently aroused interest for asparaginase production. Current assay optimizes the production of Z. mobilis asparaginase by continuous fermentation using response surface experimental design and methodology. The studied variables comprised sucrose, yeast extract and asparagine. Optimized condition obtained 117.45 IU L-1 with dilution rate 0.20 h-1, yeast extract 0.5 g L-1, sucrose 20 g L-1 and asparagine 1.3 g L-1. Moreover, carbon:nitrogen ratio (1:0.025) strongly affected the response of asparaginase activity. The use of Z. mobilis by continuous fermentation has proved to be a promising alternative for the biotechnological production of asparaginase.